2002
DOI: 10.1021/la011401a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Electrochemical Characterizations of Dilithium Octacyanophthalocyanine Langmuir−Blodgett Films

Abstract: Langmuir−Blodgett (LB) films of dilithium octacyanophthalocyanine [Li2Pc(CN)8] were first prepared, and their electrochemical reduction/reoxidation behaviors were studied in detail. An overwhelming majority of the Li2Pc(CN)8 molecules in the LB film were stacked in a face-to-face aggregated state and stood obliquely with an edge-on configuration on the substrate surface. Two overlapping redox waves were observed in the voltammogram of the LB film in 1 mol dm-3 HCl solution. Their relative intensity was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…7. These results are in good agreement with ones obtained for a novel amphiphilic phthalocyanine, 1,4-di(hydroxyethoxy)-9,10,16,17,23,24-hexapentyloxyphthalocyanine LB films [31] as well as those for LB films of dilithium octacyanophthalocyanine derivative with eight strong electron-withdrawing groups [4].…”
Section: Uv-vis Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…7. These results are in good agreement with ones obtained for a novel amphiphilic phthalocyanine, 1,4-di(hydroxyethoxy)-9,10,16,17,23,24-hexapentyloxyphthalocyanine LB films [31] as well as those for LB films of dilithium octacyanophthalocyanine derivative with eight strong electron-withdrawing groups [4].…”
Section: Uv-vis Resultssupporting
confidence: 89%
“…This extraordinary versatility makes the Pc and MPc materials as attractive candidates for a wide range of potential applications such as photovoltaic cells, molecular metals, chemical sensors, nonlinear optics, and electrochromic display devices [4][5][6][7]. MPcs have attracted interest for gas sensing applications because of their high chemical and thermal stability, their ability to be deposited as thin layers, and their high intrinsic conductivity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of monolayer films has been reported previously for macrocyclic compounds [1, 6-9, 15, 16] even though, depending on the subphase, the substrate and the specific structure of the compound, multilayer formation has also been observed [17][18][19]. Armstrong et al [17][18][19] proposed a bilayer for cooper phthalocyanine derivatives, but observed a clear transition in the isotherm that is not our case.…”
Section: Discussionsupporting
confidence: 54%
“…Armstrong et al [17][18][19] proposed a bilayer for cooper phthalocyanine derivatives, but observed a clear transition in the isotherm that is not our case. Jiao and Liu [20] reported the formation of monolayers or multilayers in naphthylidenecontaining Schiff base derivatives, depending on the compound structure.…”
Section: Discussionmentioning
confidence: 51%
“…Following the Yoneyama equation [54][55][56], the orientation angles of phthalocyanine ring in triple-decker molecules with respect to the substrate in the films of 1-5 are calculated and organized in Table 2. It is worth noting that the orientation angle of phthalocyanine ring for 1 in pure film cannot be obtained due to the very poor transfer ratio of the monolayer and the bad quality of the deposited LB film.…”
Section: Uv-vis Spectra and Polarized Uv-vis Spectramentioning
confidence: 99%